225k views
7 votes
Guys I need your HELP ASAPP!!!!!

Guys I need your HELP ASAPP!!!!!-example-1
User Hatched
by
4.9k points

1 Answer

1 vote

Answer:

HOPE THAT WAS TRUE

Explanation:


- 3 + √(m + 59) = m \\ √(m + 59) = m + 3 \\ {(m + 59)}^{ (1)/(2) } = m + 3 \\ (1)/(2) log(m + 59) = log(m + 3) \\ 0.5 log(m) + 0.5 log(59) = log(m)+log(3) \\ 0.5 log(m) = 0.5 log(59) - log(3) \\


0.5 log(m) = 0.885 - 0.477 \\ 0.5 log(m) = 0.408 \\ log(m) = 0.816


m = {10}^(0.816) = 6.556

User Gfrost
by
5.3k points